Particular pollutants, physical properties, and environmental performance of porous ceramsite materials containing oil-based drilling cuttings residues - Xiong, Deming; Wang, Chaoqiang; Huang, Xin (Environmental science and pollution research international, 2022)
The mineral compositions of oil-based drilling cutting residues (ODCRs) were similar to that of clay, which could be used as raw materials for ceramsite. In this study, the maximum addition of ODCRs and the optimum calcination conditions were studied by single factor experiment. The microstructure, phase composition, and element distribution of ceramsite were studied by means of SEM, XRD and EDS. The ceramsite, with a 40% ODCRs content, was calcined at 1000 °C for 2 h. After cooling down, the ceramsite had good physical properties, including low density, low water absorption, and high compressive strength. The bulk density was 850–970 kg/m 3 , the water absorption was 2.1–10%, and the cylinder compressive strength was 6–11.8 MPa. And most of the heavy metals in ODCRs were effectively solidified. The organic toxic substances were completely burned. The leaching amount of harmful elements met the requirements of Chinese standards. The ceramsite would avoid secondary pollution to the environment. So the ceramsite made from ODCRs can not only improve the processing speed of ODCRs, but also be used as building materials, greening materials, industrial filter materials, etc., and increase its environmental and social benefits.